Rural cult centres in the Hauran as part of a broader network of the Near East (100 BC-AD 300) - Mazzilli, Francesca (Archaeopress Roman archaeology., 2018)
This is a comprehensive multidisciplinary analysis of rural cult centres in the Hauran (southern Syria) from the pre-Roman to the Roman period (100 BC-AD 300). This volume re-evaluates the significance of contacts between the elite of the Hauran and other cultures of the Near East in shaping cult sites.